2021
DOI: 10.1101/gr.267013.120
|View full text |Cite
|
Sign up to set email alerts
|

Cellular plasticity balances the metabolic and proliferation dynamics of a regenerating liver

Abstract: The adult liver has exceptional ability to regenerate, but how it sustains normal metabolic activities during regeneration remains unclear. Here, we use partial hepatectomy (PHx) in tandem with single-cell transcriptomics to track cellular transitions and heterogeneities of ~22,000 liver cells through the initiation, progression, and termination phases of mouse liver regeneration. Our results reveal that following PHx, a subset of hepatocytes transiently reactivates an early-postnatal-like gene expression prog… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(65 citation statements)
references
References 143 publications
(162 reference statements)
4
46
0
Order By: Relevance
“…In addition, the increased proliferation capacity of midlobular/zone 2 hepatocytes may be a way to preserve liver metabolic functions, which are exerted predominantly by hepatocytes in zone 1 and 3. Supporting this, i) single-cell RNA-sequencing showed that periportal/zone 1 and pericentral/zone 3 hepatocytes maintain their metabolic competence, while midlobular/zone 2 hepatocytes proliferate after partial hepatectomy [20]; ii) ATAC-sequencing combined with RNA-sequencing showed that, after partial hepatectomy, a subset of hepatocytes retain chromatin accessibility and expression of genes involved in metabolic functions [19]. Together, this suggests that the peculiar spatial organisation allows the liver to preserve its vital metabolic functions in response to both tissue resection and toxic damage.…”
Section: Hepatocyte Functional Organisation and Spatial Geometry In Liver Regenerationmentioning
confidence: 78%
See 3 more Smart Citations
“…In addition, the increased proliferation capacity of midlobular/zone 2 hepatocytes may be a way to preserve liver metabolic functions, which are exerted predominantly by hepatocytes in zone 1 and 3. Supporting this, i) single-cell RNA-sequencing showed that periportal/zone 1 and pericentral/zone 3 hepatocytes maintain their metabolic competence, while midlobular/zone 2 hepatocytes proliferate after partial hepatectomy [20]; ii) ATAC-sequencing combined with RNA-sequencing showed that, after partial hepatectomy, a subset of hepatocytes retain chromatin accessibility and expression of genes involved in metabolic functions [19]. Together, this suggests that the peculiar spatial organisation allows the liver to preserve its vital metabolic functions in response to both tissue resection and toxic damage.…”
Section: Hepatocyte Functional Organisation and Spatial Geometry In Liver Regenerationmentioning
confidence: 78%
“…This gradient of proliferation ensures restoration of the tissue mass while maintaining liver functionality, since proliferation is associated with reduced expression of functional hepatocyte genes [4]. Proliferation is also accompanied by the transient re-acquisition of chromatin and transcriptional profiles of foetal progenitors [19] and early postnatal hepatocytes [20]. This is consistent with the fact that adult hepatocytes can de-differentiate into bipotent liver progenitors after toxic damage [21][22][23], as they are capable to give rise to both hepatocytes and cholangiocytes, resembling the liver epithelial embryonic progenitors, the hepatoblasts [2,3,24].…”
Section: Hepatocyte Functional Organisation and Spatial Geometry In Liver Regenerationmentioning
confidence: 99%
See 2 more Smart Citations
“…8C). Instead, a decrease in phosphorylated eIF2α was noted in 4-week acSRSF1 HKO and 10-day SRSF1 HKO hepatocytes, which likely reflects regeneration-associated surge in protein synthesis (54,55).…”
Section: Srsf1-deficient Hepatocytes Display Diminished Global Translationmentioning
confidence: 99%